A unified theory of happiness : an East-meets-West approach to fully loving your life - Polard, Andrea F. (Sounds True, 2012)
Combines the Western ideas of goal-setting and achievement with the Eastern idea of surrendering to the great flow of being to create a path to personal happiness.